Comparison of Gastric Cancer Risk Classifications Using Conventional and New Pepsinogen Criteria - Tae Sasakabe; Yuki Obata; Sayo Kawai; Yingsong Lin; Shogo Kikuchi (Gastroenterology Research and Practice)
Background. New serum pepsinogen (PG) criteria have been shown to indicate more accurately infection with Helicobacter pylori (H. pylori). We sought to improve risk classification for gastric cancer by adopting the new PG criteria with the addition of an H. pylori antibody test. Methods. The study participants were 275 patients with gastric cancer and 275 apparently healthy controls from case–control study data. We cross-sectionally compared the results of gastric cancer risk classifications that were based on a combination of the new PG criteria (PG II ≥ 10 ng/mL or PG I/II ≤ 5) and an H. pylori antibody test with those that were based on a combination of the conventional criteria (PG I ≤ 70 ng/mL and PG I/PG II ≤ 3) and an H. pylori antibody test. Results. Applying the conventional criteria resulted in 89 controls being classified as low risk. Applying the new criteria resulted in 23 controls (bootstrapped 95% confidence intervals [CI]: 14, 32) being additionally classified as high risk. Eight patients with gastric cancer were classified as low risk using the conventional criteria; however, six of these patients were classified as high risk by the new criteria (bootstrapped 95% CI: 2, 11). Conclusions. Compared with the conventional criteria, the new PG criteria with H. pylori antibody reduced instances of gastric cancer cases being misclassified as low risk. These findings suggest that the new PG criteria may help identify individuals at high risk of developing gastric cancer.